Shape-dependent Biodistribution of Biocompatible Silk Microcapsules - Cao, Sisi (ACS Appl Mater Interfaces, 2019)
Microcapsules are emerging as promising micro-size drug carriers due to their remarkable deformability. Shape plays a dominant role in determining their vascular transportation. Herein, we explored effect of shape of microcapsules on the in vivo biodistribution for rational design of microcapsules to achieve optimized targeting efficiency. Silk fibroin, a biocompatible, biodegradable and abundant material, was utilized as a building block to construct biconcave discoidal and spherical microcapsules with diameter of 1.8 μm and wall thickness of 20 nm. We have compared the cytocompatibility, cellular uptake and biodistribution of both microcapsules. Both biconcave and spherical microcapsules exhibited excellent cytocompatibility and internalization into cancer cells. During blood circulation in mice, both microcapsules showed retention in liver and kidney, and most underwent renal clearance. However, we observed significantly higher accumulation of biconcave silk microcapsules in lung compared with spherical microcapsules, and the accumulation was found to be stable in lung even after three days. The higher concentration of biconcave discoidal microcapsules found in lung arises from pulmonary environment, margination dynamics and enhanced deformation in blood stream. RBC-mimicking silk microcapsules demonstrated here can potentially serve as a promising platform for delivering drugs for lung diseases.